Morphoea with prominent plasma cell endoneuritis. (4th January 2017) - Singh, M.; Farquharson, N.; Owen, C.; Howat, A. J.; Singh, S.; Francis, N.; Calonje, E.
Summary: Morphoea (localized scleroderma) is a cutaneous inflammatory condition characterized by the development of indurated and discoloured plaques. The histological features of morphoea typically include a superficial and deep perivascular and periadnexal chronic inflammatory infiltrate associated with variable degrees of dermal and/or subcutaneous sclerosis. The infiltrate is typically composed of lymphocytes, macrophages and conspicuous plasma cells. The early stages of morphoea may have a very prominent inflammatory infiltrate associated with subtle sclerosis. In addition, the inflammatory infiltrate may show a perineural and rarely intraneural distribution. We report two cases of morphoea that histologically showed plasma cell endoneuritis associated with subtle dermal sclerosis. These two cases highlight the potential for diagnostic confusion with infectious and inflammatory diseases, particularly leprosy and lupus.